Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I proof the convergence of

$${\{7^{-n^{-1/5}}\}_{n\geq 1}}$$


share|cite|improve this question
Take logarithm to base 7, of the sequence $-n^{-1/5}\log 7$ and then it's limit. It'll equal the logarithm to the base 7, of the limit of the sequence because of continuity of $\log_7x$. Let the limit be $L$. Of course you can explicitly calculate $L$. $7^L$ is the required limit. – Host-website-on-iPage Jul 10 '12 at 12:18
The limit of the sequence is 1, but I have to prove the limit. – hinafu Jul 10 '12 at 12:22
up vote 3 down vote accepted

Just do some computations and use the motonicity of powers and the logarithm to find the $N$ you want:

First note, that $7^{-n^{-1/5}}\le 1$ for every $n$, now let $\epsilon > 0$. We have \begin{align*} 1 - 7^{-n^{-1/5}} < \epsilon &\iff 7^{-n^{-1/5}} > 1 - \epsilon\\ &\iff -n^{-1/5} > \log_7(1-\epsilon)\\ &\iff n^{-1/5} < \log_7\frac 1{1 - \epsilon}\\ &\iff n^{1/5} > \frac 1{\log_7 (1-\epsilon)^{-1}}\\ &\iff n > \left(\frac 1{\log_7 (1-\epsilon)^{-1}}\right)^5 \end{align*} If we let $N := 1 + \left\lceil (\frac 1{\log_7 (1-\epsilon)^{-1}})^5\right\rceil$, then $\left|{7^{-n^{-1/5}} -1}\right| < \epsilon$ for $n \ge N$.

share|cite|improve this answer
Thanks!, I will have to practice a lot from now – hinafu Jul 10 '12 at 13:00

If you're trying to prove the convergence of the given sequence, epsilon-$N$ proofs are not the only way. Sometimes, the simplifications and finding the right $N$ may be difficult. Of course if you don't know the limit of the sequence it is of no use.

I will introduce a different approach to this problem.

Consider the two functions $f:[0, +\infty] \to \mathbb{R}$ and $g:[0, +\infty] \to \mathbb{R}$ given by $f(x)=( \frac{1}{7} )^x$ and $g(x)=\sqrt[5]{x}$. Then $g(f(x))=(\frac{1}{7} )^\sqrt[5]{x}=7^{(-\sqrt[5]{x})}$ is well defined for all $x \in [0, +\infty] $ and since $f, g$ are right continuous at $0$, the limit $\lim\limits_{x \to 0+}g(f(x))$ exists and equal to $g(f(0))=7^0=1$.

It is easy to see that this result can be used to prove what you wanted to prove. We know $x \to 0+$ if and only if $ \frac{1}{x} \to +\infty$. Therefore from above we have, $\lim\limits_{x \to +\infty}7^{(-\sqrt[5]{1/x})}=\lim\limits_{x \to +\infty}7^{(-x^{(-1/5)})}=1.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.